Surfando nas ondas do Titanzinho: corpo, memória, natureza e cultura em Fortaleza (1960-2010) - Nogueira, André Aguiar (2015)
Discusses the history of the relationship between body, nature, memory and culture in the Titanzinho Beach, east coast of Fortaleza. The clipping set is located mainly in the 1960s to 2010. The Beach Titanzinho, traditional fishing area, became internationally known in the 1970s for surfing. In the 1990s, however, factors such as rapid population growth and the crime outbreak provided the end of sporting events and the location has become stigmatized in the city. More recently, with the opening of surf schools and especially with the emergence of young native champions, have changed many important aspects in the local experience. Based on orality, magazines specializing in surfing, documents from the neighborhood associations and other research sources, discusses the formation of community, suggesting the emergence of surfing as body practice that emerges from new desires and sensibilities towards nature